1998
DOI: 10.1126/science.280.5366.1077
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Identification, Mapping, and Genotyping of Single-Nucleotide Polymorphisms in the Human Genome

Abstract: Single-nucleotide polymorphisms (SNPs) are the most frequent type of variation in the human genome, and they provide powerful tools for a variety of medical genetic studies. In a large-scale survey for SNPs, 2.3 megabases of human genomic DNA was examined by a combination of gel-based sequencing and high-density variation-detection DNA chips. A total of 3241 candidate SNPs were identified. A genetic map was constructed showing the location of 2227 of these SNPs. Prototype genotyping chips were developed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
1,089
5
26

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,927 publications
(1,172 citation statements)
references
References 19 publications
28
1,089
5
26
Order By: Relevance
“…LD is a property of populations, and thus depends on the natural history of the disease gene containing a chromosome segment of the test population, and on the recombination distance between the disease gene and the test marker. LD mapping is generally performed using single nucleotide polymorphisms (SNPs), since these are more common than, and less mutable than, microsatellites [67]. In reverse genetics approaches, the genetic marker data are used to drive or refine the phenotypes, based on genetic marker data, that is, to define phenotypic groupings that are distinguished by higher rates of allele-sharing or distorsion of genetic equilibria.…”
Section: Genetic Strategy To Find Susceptibility Genes For Arhlmentioning
confidence: 99%
“…LD is a property of populations, and thus depends on the natural history of the disease gene containing a chromosome segment of the test population, and on the recombination distance between the disease gene and the test marker. LD mapping is generally performed using single nucleotide polymorphisms (SNPs), since these are more common than, and less mutable than, microsatellites [67]. In reverse genetics approaches, the genetic marker data are used to drive or refine the phenotypes, based on genetic marker data, that is, to define phenotypic groupings that are distinguished by higher rates of allele-sharing or distorsion of genetic equilibria.…”
Section: Genetic Strategy To Find Susceptibility Genes For Arhlmentioning
confidence: 99%
“…The results obtained to date in chickens indicate higher ratios than in mammals: SNPs mined from EST sequence traces gave a ratio of 2.3 [74] or 4 [39] and a survey of 138 SNPs from non-coding DNA in chickens gave a ratio of 2.36 (Vignal and Weigend, unpublished data). One probable explanation for this bias is the high spontaneous rate of deamination of 5-methyl cytosine (5mC) to thymidine in the CpG dinucleotides, leading to the generation of higher levels of C ⇔ T SNPs, seen as G ⇔ A SNPs on the reverse strand [13,80].…”
Section: Definition Of Snps and The Generation Of Single Nucleotide Pmentioning
confidence: 99%
“…The densities thus obtained are extremely high and reliability is improved by using a tiled array scheme, multiplying the number of probes used for each base position questioned [29,80].…”
Section: Direct Hybridisation Techniques: From Aso To Chipsmentioning
confidence: 99%
“…[19][20][21] Moreover, SNPs in the coding regions or the regulatory regions of genes are more likely to cause functional differences than SNPs located elsewhere. 19 Therefore, this study was undertaken to examine those possible relationship between three novel SNPs found in CDK5 promoter region and the risk of lung cancer occurrence in Korean lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%